Spontaneous embolization of an atrial septal defect occluder device into the left ventricular outflow tract in a patient with pulmonary stenosis. Issue 11 (26th October 2017) - Agca, Mustafa; Naser, Abdulrahman; Guner, Ahmet; Kılıcgedik, Alev; Celik, Mehmet; Akgun, Taylan; Alpay, Emine; Yanartas, Mehmet; Kahveci, Gokhan
Abstract : A 24‐year‐old man was admitted to our outpatient clinic for his routine checkup of consecutively percutaneously treated atrial septal defect (ASD) and pulmonary valvular stenosis 45 days ago. A 24 mm ASD occluder device was implanted under transthoracic echocardiographic guidance and 80 mm Hg peak‐to‐peak pulmonary valvular gradient decreased to 20 mm Hg gradient after pulmonary valve dilatation with 23 mm NUMED II transluminal valvuloplasty catheter balloon. Atrial septal defect (ASD) closure is now routinely performed using a percutaneous approach under echocardiographic guidance especially transthoracic echocardiography (TEE). Centrally located, ostium secundum type and less than 3.5 cm in size are considered ideal for device closure. Although there is considerable variation in size and location of the defects, TEE guidance is quite important for this proportion of ASDs. The selection of patients for percutaneous transcatheter closure of a secundum ASD requires accurate information regarding the anatomy of the defect such as its maximal diameter and the amount of circumferential tissue rims.